Variable step-size oscillator-based adaptive notch filer algorithm using maximum correntropy criterion - Baek, H.J; Cho, J; Shin, J.W (Electronics letters, 2018)
A novel oscillator-based adaptive notch filter (OSC-ANF) algorithm is presented. The proposed algorithm has robustness against the impulsive noise because it is derived by using the maximum correntropy criterion (MCC). In addition, the variable step-size MCC-OSC-ANF algorithm is proposed to improve the frequency estimation performance. Experimental results show that the proposed algorithms perform better than the previous algorithm under impulsive noises.